Macrophages in malignant pleural effusions – alternatively activated tumor associated macrophages - Kaczmarek, Mariusz; Sikora, Jan (Contemporary Oncology/Współczesna Onkologia, 2012)
Pleural macrophages are involved in local defense mechanisms against environmental pollution, bacteria and cancer. Their main function encompasses phagocytosis of degenerated mesothelial cells. In human pleural effusions macrophages represent more than half of all cells. A model of polarized macrophage activation (M1 and M2) was proposed, which defines a functionally different macrophage populations generated in response to various factors present in the inflamed environment. Tu-mor associated macrophages are a major component of the inflammatory infiltrate of most cancers. They can promote the proliferation and spread of cancer cells in the early stages of carcinogenesis and during metastasis. Macrophages isolated from malignant pleural effusions as well as tumor associated macrophages exhibit weak cytotoxic activity against tumor cells, increase their proliferative activity and may protect tumor cells from apoptosis. Defining biology of macrophages present in specific environment of the pleural effusion could allow the introduction of innovative diagnostic and therapeutic strategies.